Enhancing Local Economic Independency by Issuing Local Government Bond: Comparing Japan and Indonesia - Alen Ermanita (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2017)
For more than a decade, Indonesia has been practicing decentralization. During this period, local governments still experience difficulties in generating local revenues to fund their development. Local government bonds (LGBs) are actually one of the finest sources for financing local development. However, until now there is no real practice in issuing local bonds in Indonesia though it is allowed in the existing regulation. There are still many considerations which hindered the realization of LGB issuance ranging from the rule of mechanism to the local governments’ readiness themselves. To gain more insights about the issue, learning from another country (in this case: Japan) on how they manage LGBs effectively and securely will be beneficial. Comparison model between the two countries is chosen to see the regulation and managerial aspects in LGB implementation including the main institution in central level, rules of the game, buyers and purposes. By having this comparison, it is expected that some crucial factors can be looked at, which may then provide us some information on why LGBs are yet to bloom in Indonesia. Moreover, the comparison is expected to provide some basics about the possibility to ease policy adoption for Indonesia in managing LGBs.